الدراسة النظرية للخصائص الضوئية للملونات العضوية في الخلايا الشمسية - نورالوئام, جعفور; ركبية, زغيدي; ايناس, بن عطاء الله (University of El-Oued, 2022)
"In our topic, we dealt with a theoretical study on photovoltaic solar cells in their various fields of use. Its manufacture has gone through a large number of improvements from one generation to the next on the basis of low cost and high efficiency. Then we touched on the composition of organic dyes, which are widely used, especially in the textile industry, due to their chemical stability and ease of installation. However, it is considered a source of pollution once it is discharged into the environment. And we concluded our study with a previous study related to the experiments carried out on UV photolysis and coupling (UV/H2O2)to décompose four Dyes: Meo, Rme, BBP, and BBT. ""تناولنا في موضوعنا دراسة نظرية حول الخلايا الشمسية الكهروضوئية بمختلف مجالات استخداماتها. حيث مر تصنيعها من خلال عدد كبير من التحسينات من جيل إلى آخر على أساس التكلفة المنخفضة و الكفاءة العالية. ثم تطرقنا إلى تركيب الملونات العضوية و التي تستخدم على نطاق واسع و خاصة في صناعة النسيج نظرا لاستقرارها الكيميائي و سهولة تركيبها. و مع ذلك، تعتبر مصدر للتلوث بمجرد تصريفها في البيئة. و ختمنا دراستنا بدراسة سابقة متعلقة بالتجارب التي أجريت على التحلل الضوئي للأشعة فوق البنفسجية و اقتران (UV/H2O2) لتحلل أربع ملونات: Meo, Rme, BBP, BBT "
مذكرة ماستر تخصص هندسة طرائق
Keywords: Cellules solaires photovoltaïques, haut rendement, colorants organiques, rayons ultraviolets.; "الخلايا الشمسية الكهروضوئية، الكفاءة العالية، الملونات العضوية، الأشعة فوق البنفسجية. "